Timber yielding plants and their utilities in Nizamabad district of Andhra Pradesh - Dinesh, Vijigiri; Sharma, P P (Journal of Phytology, 2012)
Trees are important to humankind not only economically, environmentally and industrially but also spiritually, historically and aesthetically, for they support human life through various means by providing a wide range of products for survival and prosperity. Trees are mostly used for timber purposes. The present ethno-botanical explorations conducted in forest areas of Nizamabad resulted in the information on the timber yielding plants used for different purposes. Information gathered from Nizamabad district indicates that the tribals and other village people of this region possess good knowledge of plants used for different purposes, but their continuous and progressive exposure to modernization may result in extinction of such rich heritage of knowledge in the course of time. Besides medicine, food, fiber plants which yield timber are extensively used in the region for various purposes. The Present communication deals with 49 species of timber yielding plants which belong to 27 families.